Application of geographical information system and remote sensing for investigating malaria’s footprint: a case study of Iwo Metropolis, Nigeria - Joseph Olajuwon Dada; Sodiq Babatunde Rajee; Wasiu Adelani Rasak; Ayodeji Olatunbosu Ajani; Ismail Abdulraheem; Olayemi Balikis Shodeinde; Ibrahim Ademola Fetuga (The Journal of Engineering and Exact Sciences)
On a worldwide scale, the challenge posed by malaria fever has long been acknowledged as a significant peril to the global population. Nigeria, being situated within a tropical climate, has experienced an especially profound impact. The imperative to closely monitor this lethal disease cannot be overstated. Therefore, this research employs a comprehensive methodology that combines Geographic Information System (GIS) techniques with Epidemiology. The primary objective is to create a malaria risk map specifically for Iwo Metropolis while also gauging the extent of susceptibility within the region. Ultimately, the aim is to diminish the occurrence of malaria by implementing suitable medical interventions. The objectives of this study are the creation of spatial database for the entities in the study area, performing spatial analyses on the database created; and analyzing the spread of malaria disease based on environmental factors in Iwo Local government and finally to generate Malaria Risk Map. This research work was designed to examine and analyze the incidence of malaria and clearer understanding of geographic distribution of malaria-infected people and locations of such inhabitants to the health facility being essential for monitoring the prevalence and for providing treatment, care and support services to the affected area. The study adopted the primary method of data collection using Global positioning system (GPS) to pick point locations of areas where malaria is prevalent and the locations of the different hospitals within Iwo metropolis. Also, topographic maps were collected from SAS planet and Google Earth and secondary data from the State General Hospital, Iwo, where malaria data of adults above 18 years were collected which is divided into old and new cases. In the build- up of this project, the data collected were then uploaded to ArcGIS 10.8, this software was used to perform spatial analysis like buffering operation, service area, trend analysis and neighborhood operation. This project is aimed at producing digital or hard copy maps showing malaria patterns in form of high and low risk areas in order to determine areas that require quick intervention programs.